Remaja, Seksualitas dan Manajemen Nafsu (Tafsir Tematik Q.s. Yusuf [12]: 22-23) - Muhammad A’raaf; Taufik Ramadhan Suparman (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2022)
This paper tries to reveal the method applied by Prophet Yusuf in controlling lust. In previous studies, interpreters and researchers did not associate verses 22-23 of surah Yusuf with adolescents and sexual desires, especially at that time and only focused on tarbawi (education) values. This discussion is necessary considering that the Prophet Yusuf did manage to resist the temptation of sexual desire and save him from destruction. The method used in this study is qualitative with an analysis interpretation approach. In these verses, it is concluded that in managing lust, there are at least three foundations and three ways that need to be owned and done by teenagers to subdue lust.